2004
DOI: 10.1159/000075074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Enteral Nutrients on Bacterial Translocation in Experimental Obstructive Jaundice

Abstract: Obstructive jaundice leads to bacterial translocation (BT) by disruption of the gut barrier, intestinal microecology, and impaired host immune defence. The objective of the present study is to investigate the effects of different enteral nutrients on BT that is induced by obstructive jaundice in rats. Eighty male Wistar-Albino rats were randomly assigned into 4 groups. Group 1: 20 rats underwent laparotomy, common bile duct (CBD) was not actually ligated and transected, but sham ligation of CBD was performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 42 publications
1
17
1
2
Order By: Relevance
“…The results of our experiments on bacterial translocation in glutamine-treated animals agree with those of recent studies which showed that glutamine administration in BDL animals is associated with reduced live bacterial translocation [22][23][24][25] . Our study further demonstrates that glutamine treatment is associated with signifi cant reductions in the translocation of non-viable labelled bacterial products from the gut.…”
Section: Discussionsupporting
confidence: 91%
“…The results of our experiments on bacterial translocation in glutamine-treated animals agree with those of recent studies which showed that glutamine administration in BDL animals is associated with reduced live bacterial translocation [22][23][24][25] . Our study further demonstrates that glutamine treatment is associated with signifi cant reductions in the translocation of non-viable labelled bacterial products from the gut.…”
Section: Discussionsupporting
confidence: 91%
“…Clinically, it leads to an increase in liver function tests (11,17). UDCA and TUDCA lead to an improvement in liver function tests.…”
Section: Discussionmentioning
confidence: 99%
“…In cholestasis emerging after biliary obstruction, the RES seems to be ruined and phagocytic function is depressed. Kupffer cell activation plays a basic role at the beginning of an efficacious immune response (5,8,11,17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations